INTERNALISASI NILAI PERAJIN BATIK GEDOG DALAM PELESTARIAN IDENTITAS BUDAYA LOKAL MELALUI PENDIDIKAN KELUARGA DI DESA MARGOREJO KABUPATEN TUBAN - Defriska Salsabila Ardhana; Kukuh Miroso Raharjo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the role of family education in transmitting skills and internalizing the cultural values of Batik Gedog in Margorejo Village, Tuban Regency. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and documentation involving Batik Gedog artisan families who have maintained the tradition across generations. The findings reveal that the family serves as the primary space for transmitting batik-making skills through the direct involvement of children in daily activities. The transmission process occurs informally through habituation, modeling, and continuous family interaction. Values such as perseverance, responsibility, cooperation, and commitment to cultural heritage are gradually internalized and shape the character of the younger generation. The novelty of this study lies in highlighting the role of family education as the main mechanism for internalizing cultural values in sustaining the Batik Gedog tradition. Although modernization and the growth of industrial batik present challenges to the sustainability of the tradition, the stability of family-based education remains the main supporting factor for cultural preservation. Therefore, strengthening family education based on local cultural values should be considered in educational policies and cultural preservation efforts.